"Double guarantee mechanism" of Ca2+-intercalation and rGO-integration ensures hydrated vanadium oxide with high performance for aqueous zinc-ion batteries. Issue 1 (5th November 2020) - Hu, Tao; Feng, Ziyi; Zhang, Yifu; Liu, Yanyan; Sun, Jingjing; Zheng, Jiqi; Jiang, Hanmei; Wang, Peng; Dong, Xueying; Meng, Changgong
Abstract : Ca 2+ -Intercalated hydrated V2 O5 /rGO (CaVOH/rGO) is synthesized via a facile hydrothermal process and applied as a cathode for ARZIBs with an admirable specific capacity (409 mA h g −1 at 0.05 A g −1 ) and excellent energy density (381 W h kg −1 ). Abstract : Aqueous rechargeable zinc-ion batteries (ARZIBs) are widely considered to be potential energy storage devices because of their low toxicity, low cost and environment-friendliness. Recent studies have proved that hydrated vanadium oxides are significant cathode materials for ARZIBs. However, their low specific capacity and poor cycling stability limit their further development because of the structural instability of the resulting device. In this work, we developed a "double guarantee mechanism" composite of Ca 2+ -intercalated hydrated vanadium oxide (V2 O5 · n H2 O, abbreviated as VOH) integrated with reduced graphene oxide (rGO), denoted as CaVOH/rGO, via a facile hydrothermal process and subsequent freeze-drying method. The inserted Ca 2+ expanded the layer spacing, greatly reduced the electrostatic interactions and increased the reversibility of the vanadium oxide, while the integrated graphene improved the conductivity and made the composite material stable during the discharge/charge process with outstanding electrochemical performances. The CaVOH/rGO//Zn battery delivered an exceptional specific capacity of 409 mA h g −1 at 0.05 A g −1 . It also exhibited an admirable capacity retention of more than 90% (299 mA h g −1 ) after 2000 cycles at 4.0 A g −1 and an impressive energy density (381 W h kg −1 at 48 W kg −1 ). To determine the main reaction mechanisms of Zn 2+ reversible (de)intercalation, we employed multiple ex situ analytical methods to reveal the process of Zn 2+ storage. The results illustrated that the CaVOH/rGO three-element composite has marvelous potential as a cathode material, and this work provides a novel method to enhance the electrochemical properties of V2 O5 · n H2 O.